A simple colorimetric and ratiometric fluoride ion probe with large color change. Issue 1 (21st December 2020) - Shi, Heng; Chen, Hongjin; Li, Xiangguo; Xing, Jieni; Zhang, Gang; Zhang, Rui; Liu, Jian
Abstract : Two colorimetric and ratiometric fluoride ion probes SHJ-1 and SHJ-2 based on the acylhydrazone skeleton have been developed. Abstract : Two colorimetric and ratiometric fluoride ion probes SHJ-1 and SHJ-2 based on the acylhydrazone skeleton have been developed. Among the eight anions (F −, Cl −, Br −, I −, ClO4 −, H2 PO4 −, HSO4 −, CH3 COO − ), the present probes showed high selectivity and sensitivity toward fluoride ion detection with obvious color change. Notably, the probe SHJ-1 exhibited a red shift of 145 nm upon fluoride sensing, which is the largest value among fluoride ion probes based on acylhydrazone derivates to date. 1 HNMR titration study and theoretical calculations suggested that the strong binding of the probe SHJ-1 to fluoride as well as the further deprotonation may facilitate the intramolecular charge transfer transition. These two probes are 1 : 1 complexed with fluoride ions, and the detection limits were calculated to be 1.24 μM for SHJ-1 and 15.73 μM for SHJ-2 .